Comparison of Two Natural Surfactants for Pulmonary Hemorrhage in Very Low-Birth-Weight Infants: A Randomized Controlled Trial - Bozdağ, Şenol; Dilli, Dilek; Gökmen, Tülin; Dilmen, Uğur (American Journal of Perinatology, 2015)
Objective To compare the efficacy of two natural surfactants for pulmonary hemorrhage in very low-birth-weight (VLBW) infants.Study Design A prospective randomized controlled trial was conducted on 42 infants who were divided into two groups, poractant alfa (n = 21) and beractant (n = 21).Results In both the groups, the mean standard deviation (SD) birth-weight and gestational age were similar (p = 0.33 and 0.89, respectively). Although, the mean oxygenation index (OI) increased after pulmonary hemorrhage compared with baseline value and decreased after surfactant in both groups, variations in OI were more prominent in poractant alfa group (before hemorrhage: 11.9, after hemorrhage: 22.7, 1 hour of surfactant: 14.6, 8th hour of surfactant: 7.8, 24th hour of surfactant: 8.5, p = 0.007 vs. before pulmonary hemorrhage:11.1, after pulmonary hemorrhage: 17.9, 1 hour of surfactant: 12.8, 8th hour of surfactant: 12.8, 24th hour of surfactant: 9.7, p = 0.02). There was no significant difference between the groups for OI values at all time points (p > 0.05). The rates of bronchopulmonary dysplasia (BPD) and mortality related to pulmonary hemorrhage were similar in both the groups.Conclusion Both natural surfactants improved oxygenation when administered for pulmonary hemorrhage in VLBW infants. The type of surfactant seems to have no effect on BPD and mortality rates in these patients.
Keywords: premature; pulmonary hemorrhage; surfactant